A 37 mm Spindle Cell Lipoma on the Floor of the Mouth. (4th August 2019) - Malthiery, Eve; Costes-Martineau, Valérie; Fauroux, Marie-Alix; Torres, Jacques-Henri
Abstract : Spindle cell lipoma (SCL) is a rare variety of lipoma that mostly arises in male patients and rarely affects the oral cavity. The floor of the mouth is an uncommon site for SCL, and very few cases have been reported in this location. A case of SCL is reported in a 70-year-old woman who had noticed a swelling of the floor of the mouth without any functional consequence. Both ultrasonography and RMI suggested a diagnosis of ranula, whereas clinical palpation showed a nonfluctuant mass. The lesion was excised under local anesthesia. A37 × 32 mm encapsulated yellow mass was removed. Histological features (mature adipocytes and CD34+ spindle cells) led to a diagnosis of SCL. Medical imaging assessment of this lesion could have been influenced by the high frequency of the ranulas in the floor of the mouth. This case appears to be quite infrequent because of its location (floor of the mouth), its size (over 3.5 cm), and the patient's gender (female).